BASIC CHARACTERISTICS OF THE PLUVIOMETRIC REGIME IN THE UNA RIVER BASIN - Aida, Korjenić; Emir, Temimović; Amra, Banda; Amina, Sivac (International Journal of Research -GRANTHAALAYAH, 2018)
Intensity of action and frequency of high and low pressure barometric fields of large and medium scale have great influence on dynamics of pluviometric regime. On their action depend characteristics of thermic regime, relative humidity, cloudiness and windiness, which directly affect the precipitation. Concerning that the water balance is difference between the inflow and evaporation, it comes that precipitations do not have just special role, but they are also the most important factor of the Una river regime. Disposition and precipitation structure are the river regime's essential assumptions, so at the same annual height of precipitation, we have more water in rivers in the year with more precipitations during the colder period. Then we have less evaporation so the inflow from the basin is bigger. The amount and disposition of the precipitation in the Una River basin is analyzed in this paper in order to define the pluviometric regime of this area. Pluviometric regime greatly influences the Una river regime and water balance, what was the reason for this analysis and further hydrological research in the Una River basin.